2020
DOI: 10.1080/14786419.2020.1795655
|View full text |Cite
|
Sign up to set email alerts
|

Constituent composition of the essential oils from some species of the genus Saussurea DC

Abstract: Constituent composition of the essential oils from some species of the genus Saussurea DCThe genus Saussurea DC is well known for its rich chemical composition and wide range of biological activities. Although content and biological effects of major chemical components are thoroughly studied, the composition and concentrations of minor constituents, such as essential oils, still remains unclear. In total, 62 different chemical compounds have been identified in the essential oils from S. controversa, S. latifol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Saussurea costus is an herb used in many traditional medicine systems to treat asthma, inflammatory diseases, ulcers, and stomach problems [ 25 , 26 ]. Furthermore, several laboratory and animal model studies have demonstrated that Saussurea costus shows anti-inflammatory, anti-trypanosomal, potent anticancer, antibacterial, antifungal, and antiviral activity, confirming its tradition of use in various forms of medicine [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 88%
“…Saussurea costus is an herb used in many traditional medicine systems to treat asthma, inflammatory diseases, ulcers, and stomach problems [ 25 , 26 ]. Furthermore, several laboratory and animal model studies have demonstrated that Saussurea costus shows anti-inflammatory, anti-trypanosomal, potent anticancer, antibacterial, antifungal, and antiviral activity, confirming its tradition of use in various forms of medicine [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 88%
“…The genus Saussurea DC (family Asteraceae) is represented by about 500 species, which are widespread in Eurasia and North America and have long been used in folk medicine in the form of single- and multi-component herbal preparations. More than 200 compounds have been isolated and identified from Saussurea genus members, including phenylpropanoids, sesquiterpenoids, flavonoids, phytosterols, triterpenoids, lignans, coumarins, ceramides, and polysaccharides [ 1 , 2 , 3 ]. Extracts from Saussurea plants have been reported to exhibit anti-inflammatory, antioxidant, anti-cancer, anti-arthritic, and circulatory effects [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Asteraceae) have antimicrobial, anti-parasitic and anti-inflammatory activity attributed to the sesquiterpene lactones, [3][4][5][6] which biogenesis is similar to the oxygen-containing sesquiterpenoids. [3] The essential oil from Saussurea is widely used in traditional Chinese and Indian medicine as a single drug or in combination with other naturally occurring substances. [3,5] Saussurea lappa Clarke, known as Kuth root or costus, belongs to family Asteraceae (Compositae).…”
Section: Introductionmentioning
confidence: 99%
“…[3] The essential oil from Saussurea is widely used in traditional Chinese and Indian medicine as a single drug or in combination with other naturally occurring substances. [3,5] Saussurea lappa Clarke, known as Kuth root or costus, belongs to family Asteraceae (Compositae). [7] Oil from the roots used in traditional medicine and perfumes.…”
Section: Introductionmentioning
confidence: 99%